SYNTHESIS AND STUDYING OF STRUCTURE AND OPTICAL PROPERTIES OF TiO2 - Ag NANOCOMPOSITE - Marina S. Shama; Alexander A. Kravtsov; Andrey V. Blinov; Maria A. Jasnaja; Daria G. Selemeneva (Вестник Северо-Кавказского федерального университета, 2022)
Nanoparticles of titanium oxide and nanocomposites based on it were synthesized by the sol-gel method for different values of pH range. Structure and optical properties of the obtained materials were studied by IR spectroscopy, X-ray diffraction analysis and diffuse reflectance spectroscopy. Revealed dependence of the band gap of TiO2 composites from calcination temperature and pH of the synthesis.